Hubungan Antara Riwayat Pekerjaan Dengan Derajat Osteoarthritis Pada Wanita Usia Di Atas 65 Tahun - Deni Prasetyo Utomo; Dhoni Akbar Ghozali; Rhyan Darma Saputra; Udi Heru Nefihancoro (Plexus Medical Journal, 2022)
Introduction: Osteoarthritis is a chronic degenerative disease characterized by pain and joint cartilage damage. Osteoarthritis is a disease that disrupts the homeostasis of cartilage metabolism so that it damages the proteoglycan structure in cartilage caused by age, excessive joint wear, anatomic defects, mechanical or chemical stress, obesity, genetics and humoral. Osteoarthritis generally occurs in the knees, feet, shoulders, hands, spine, and hips. Certain work conditions that require more strenuous physical movements such as lifting heavy weights and going up and down stairs are a risk factor for osteoarthritis. The purpose of this study was to determine the relationship between work history and the degree of osteoarthritis in women aged over 65 years. Methods: This is an analytical observational research with cross sectional study design. The Subject in this research is medical record patient RSUD DR MOEWARDI SURAKARTA Hospital who have met the criteria. Sampling was done using simple random sampling technique. Data was collected and then analyzed using Spearman correlation test. Results: The analysis result from 46 samples using Spearman correlation test obtained a p value of less than 0.05 indicating that there is a significant relationship between work history and the degree of osteoarthritis in women aged over 65 years. Conclusion: There is a significant relationship between work history and the degree of osteoarthritis in women aged over 65 years. Keywords: Osteoarthritis; Occupational History; Degree of OA